Radical Islam in East Africa - Rabasa, Angel (RAND Corporation, 2009)
American geopolitical interests and the potential threats to those interests are both on the rise in East Africa. The author places the spread of militant Islamism and the development of radical Islamist networks in East Africa in the broader context of the social, economic, and political factors that have shaped the region's security environment.